Maternal and Fetal Outcome in a Patient with Buccal Embryonal Rhabdomyosarcoma - Wafa M. Fageeh,; Ossama H. Raffa, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Rhabdomyosarcoma is a rare malignancy that develops primarily in young individuals. We report a 19-year-old female with rhabdomyosarcoma who was classified with stage IIA disease, based on the clinical grouping system developed by the Intergroup Rhabdomyosarcoma Study Group in 1972. The patient was treated with surgery and chemotherapy. The histopathological and radiological assessment showed no residual tumor in adjacent tissues to contradict the clinical classification. The patient was scheduled for radiotherapy but left against medical advice and returned pregnant six months later with recurrence. She chose not to terminate the pregnancy, restricting the treatment options to chemotherapy. At 32 weeks of gestation, she underwent a caesarean section due to fetal distress. The patient deteriorated and passed away shortly after. The baby, however, is healthy. Although recent modalities of combined surgery, chemotherapy, and radiotherapy have improved the survival of such malignancies, they still have poor outcomes when during a pregnancy.